Studies on the metabolic effects of iron deficiency anemia liver gluconeogenesis and muscle glycolysis - Olagunju, Joseph A.
Studies on the metabolic effects of iron-deficiency anemia on liver gluconeogenesis and muscle glycolysis in female albino rats of the Sprague-Dawley strain were done. Anemic iron-deficient rats showed increased activities of liver glutamate-pyruvate transamirase, fructose 1,6-diphosphatase and glucose-6-phosphatase. Compared to the controls, the concentration of liver glycogen was higher one hour after the intraperitoneal injection of L-alanine. These data indicate increased gluconeogenesis in the liver of the anemic rats. In diaphragm muscle, the activities of hexokinase, pyruvate kinase, and glutamate-pyruvate transminase were increased. The increase in hexokinase and more importantly, pyruvate kinase, indicate an increase in glycolysis since these enzymes catalyze irreversible steps in the pathway. The increase in GPT indicate increased synthesis of alanine as a means of disposing part of the pyruvate whose biosynthesis is enhanced by the increased activity of pyruvate kinase and to remove the amino groups of amino acids whose catabolism is probably increased in muscle. This is supported by the increased levels of serum alanine and by the decreased concentrations of supernate protein in the diaphragms of iron-deficient animals. Lactate dehydrogenase activity in diaphragm muscle was comparable in all the experimental groups. The adrenal glands were enlarged relative to body weight.
Theses--(Master in Science in Biochemistry) University of the Philippines Manila
Keywords: Iron Deficiency Anemia; Anemia; Gluconeogenesis; Glucose